The Relationship Between Family Support and Medication Adherence in Type 2 Diabetes Patients at Cililin Hospital, Bandung, Indonesia - Yayu Kartini; Tonika Tohri; Mawar Puspa Warna (Knowledge Dynamics, 2024)
Background: Diabetes mellitus is often called the silent killer and often causes complications for sufferers that require long-term treatment. Family support is the involvement provided by the family to the patient which includes a positive attitude, affirmation and assistance. Compliance is the degree to which patients carry out treatment methods and behavior recommended by health workers. This study aims to determine the relationship between family support and medication adherence to type 2 diabetes mellitus patients at the internal medicine polyclinic of Indonesian Hospital. Methods: Categorical comparative analysis in 2 groups was not paired with a cross-sectional approach. The population in this study is 325 respondents. Sampling was determined using the purposive sampling technique as many as 77 respondents who met the criteria. The instruments in this study used the Nursalam social family support questionnaire and the MMAS-8 (Morisky Medication 8-item Adherence Scale) questionnaire. Data analysis used univariate and bivariate analysis with the Fisher Exact test. Results: The results of the fisher exact test obtained a p-value of 0.00 or <0.05, namely there was a relationship between family support and medication adherence in type 2 diabetes mellitus patients. Conclusion: There is a significant relationship between family support and medication adherence in patients with type 2 diabetes mellitus at the internal medicine polyclinic of Cililin Hospital.